Molecular identification and characterization of Sarcocystis spp. in horsemeat and beef marketed in Japan - Murata, Rie; Suzuki, Jun; Hyuga, Ayako; Shinkai, Takayuki; Sadamasu, Kenji (Parasite (Paris), 2018)
Human Sarcocystis infections are known to be caused by the ingestion of raw or undercooked beef or pork containing mature sarcocysts of Sarcocystis hominis or S. suihominis , respectively. In addition, several cases of parasitic food poisoning in Japan have recently been reported after consumption of raw horsemeat containing sarcocysts of S. fayeri . In this study, the presence of sarcocysts in 28 horsemeat and 121 beef samples collected in Tokyo was investigated. Sarcocysts of S. fayeri were found in 16 horsemeat samples. Sarcocysts of S. hominis were not detected in beef samples, while sarcocysts of S. cruzi were detected in 60 beef samples. In addition, S. hirsuta and S. bovini were isolated only from New Zealand beef samples. Bradyzoites in sarcocysts collected from 62/73 sarcocyst-positive refrigerated horsemeat and beef samples were determined to be viable. Molecular analysis of S. fayeri 18S rRNA gene sequences revealed that intraspecific variation among eight individual bradyzoites from a single sarcocyst was as high as 9.8%. In contrast, mitochondrial cytochrome c oxidase subunit 1 (mtDNA cox1 ) gene sequences from the six fragments of a single sarcocyst were 100% identical. Sarcocysts of S. bovini isolated from beef also exhibited intraspecific variation in 18S rRNA gene sequences and had to be cloned before sequencing, while mtDNA cox1 gene sequences were obtained by direct sequencing. Therefore, we conclude that molecular analysis of the mtDNA cox1 gene is the most useful for identification of Sarcocystis species. This study provides the first published partial sequence of the S. fayeri mtDNA cox1 gene. Les infections humaines par Sarcocystis sont causées par l’ingestion de viande de bœuf ou de porc, crue ou insuffisamment cuite, contenant des sarcocystes mûrs de Sarcocystis hominis ou de S. suihominis , respectivement. En outre, plusieurs cas d’intoxication alimentaire parasitaire ont récemment été signalés au Japon après consommation de viande de cheval crue contenant des sarcocystes de S. fayeri . Dans cette étude, la présence de sarcocystes dans 28 échantillons de cheval et 121 échantillons de bœuf collectés à Tokyo a été étudiée. Des sarcocystes de S. fayeri ont été trouvés dans 16 échantillons de viande de cheval. Des sarcocystes de S. hominis n’ont pas été détectés dans les échantillons de bœuf, alors que des sarcocystes de S. cruzi ont été détectés dans 60 échantillons de bœuf. De plus, S. hirsuta et S. bovini n’ont été isolés qu’à partir d’échantillons de bœuf néo-zélandais. Les bradyzoïtes des sarcocystes prélevés sur 62/73 échantillons de viande de cheval et de viande de bœuf réfrigérés positifs aux sarcocystes ont été jugés viables. L’analyse moléculaire des séquences du gène de l’ARNr de S. fayeri a révélé que la variation intraspécifique entre huit bradyzoïtes individuels d’un seul sarcocyste atteignait 9,8 %. En revanche, les séquences du gène de la sous-unité 1 de la cytochrome c oxydase mitochondriale (ADNmt cox1 ) provenant des six fragments d’un seul sarcocyste étaient identiques à 100 %. Les sarcocystes de S. bovini isolés du bœuf présentaient également une variation intraspécifique des séquences du gène de l’ARNr 18S et ont dû être clonés avant le séquençage, tandis que les séquences du gène cox1 ont été obtenues par séquençage direct. Par conséquent, nous concluons que l’analyse moléculaire du gène cox1 est la plus utile pour l’identification des espèces de Sarcocystis . Cette étude fournit la première séquence partielle publiée du gène cox1 de S. fayeri .